Marxism for Malayans - Parkinson, C. Northcote (Cyril Northcote), 1909-1993; Marx, Karl, 1818-1883. (Singapore : D. Moore, 1956)
PREFACE This work is based upon three public lectures delivered at the University of Malaya in 1955; lectures designed for the general public as well as for members of the University. These lectures were on Marxism and had no special reference to Malaya. They were academic, planned neither to uphold nor to disprove Marxist theory but merely to explain who Karl Marx was, what he taught and with what effect. In printing them, however, for general circulation, it has seemed best to go a little beyond the scope of the lectures as delivered. I have written, therefore, an historical introduction showing briefly the circumstances in which socialist doctrines have arisen. I have tried, more particularly, to show where socialism ends and where communism begins. Chapters I, II and III are the lectures in very much their original words. To these I have added Chapter IV, containing a short account of Marxism in Malaya and ending with an attempt to assess the chances (and the results) of a communist victory. I have given my reasons for thinking that Malaya will remain free of Marxist domination. I can pretend to no great impartiality in this matter, thinking as I do that political and economic affairs are better guided by reason than by religious dogma. Nothing that I have written will make a Marxist doubt the truth of Karl Marx's revelation. I may hope, however, to have shed a little light on what his teachings were. Whether initially friendly or hostile towards the Marxist scripture wel need at least to know what it contains. We also need to know exactly when Karl Marx was writing his works and against what background of experience and of human affairs. We need finally to ask ourselves whether his views are entirely relevant to a different land at a later period in history. If they are not it may be that we shall be wiser to do our own thinking. While, however, we may find that the better plan, I do not believe that Marxism can be wholly ignored. The Marxists have a message for us and I have completed my last chapter by trying to explain what I think that message is. Only in that very limited sense do I recommend Marxism for Malayans. C. NORTHCOTE PARKINSON.
PREFACE -- INTRODUCTION -- Chapter I. Marx the Man -- Chapter II. Marx the Thinker -- Chapter III. Marx the God -- Chapter IV. Marx in Malaya
2Based upon three public lectures delivered at the University of Malaya in 1955.3.
Koleksi Sumbangan : Dr. Syed Husin Ali
Keywords: Communism; Communism -- Malaysia -- Malaya; Malaya -- Politics and government